2021
DOI: 10.1002/pc.26405
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of Abaca fiber and Kevlar fibers based brake friction composites

Abstract: WHO and Environment protection agencies have reported that the trending brake pad materials are harmful to human health. These materials (Asbestos and Kevlar) produce toxic gases when used in brake pad composites. It is a cause of lung cancer, mesothelioma, affects the respiratory system, and causes many diseases. It has been causing many million people's death. Kevlar (aramid) is the trending material used in the brake pads. So, it is necessary to find a substitute for these toxic elements. In this direction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…[ 12–15 ] Asbestos use has been restricted by the WHO after learning of its side effects. [ 11,16–21 ] This reinforced material has drawbacks, including a low recycling rate, high cost, and environmental toxicity. Many studies have revealed that Kevlar has a significant negative impact on human health.…”
Section: Introductionmentioning
confidence: 99%
“…[ 12–15 ] Asbestos use has been restricted by the WHO after learning of its side effects. [ 11,16–21 ] This reinforced material has drawbacks, including a low recycling rate, high cost, and environmental toxicity. Many studies have revealed that Kevlar has a significant negative impact on human health.…”
Section: Introductionmentioning
confidence: 99%
“…Many research articles show the importance of organic fibers in many applications. [6][7][8][9][10][11][12][13][14][15] Some papers have reported that natural fibers have been experimented with to replace asbestos and aramid fibers. Natural fiber has good mechanical, physical, and chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Natural fiber has good mechanical, physical, and chemical properties. [16,17] Kevlar has now replaced asbestos and has excellent braking properties, but research has shown its negative impact. The use of asbestos started by keeping its advantage of excellent braking properties, although further research has found that it leads to various kinds of cancer and causes serious lung disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self‐lubricating fabric composite are mainly composed of thermosetting resin and hybrid fabric weaved by two or more kinds of high‐performance fiber. [ 1–4 ] Self‐lubricating fabric composite have the advantage of maintenance‐free, low friction, long service life, and low weight. [ 5–7 ] It can be used in spherical joint bearing, landing gear, and aeroengine of aircraft to play the role of load‐bearing, anti‐wear, and antifriction.…”
Section: Introductionmentioning
confidence: 99%